1977
DOI: 10.1258/002367777781005433
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of vascular and muscular changes in ascorbic acid deficient guinea-pigs

Abstract: Disorganization of muscle structures such as fragmentation of myofilaments with a loss of contrast in the Z bands, swelling of mitochondria and glycogenic infiltration, was seen in ascorbic acid deficient guinea-pigs. Vacuolar degeneration of external and internal endothelial cell membranes with accompanying dystrophic changes of the surrounding muscle and lack of collagen formation were consistent findings. Chondroblasts showed a marked dissolution of the matrix vesicle and a lack of hyaline droplets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As such, Lepr db/+ Smp30 Y/− and Lepr db/db Smp30 Y/− mice were given vitamin C-supplemented water in this study. Vitamin C is known to play an important role in the structure and function of mitochondria and endoplasmic reticulum [33]. Harrison et al reported that vitamin E and vitamin C treatment improves fibrosis but not necroinflammation in NASH patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…As such, Lepr db/+ Smp30 Y/− and Lepr db/db Smp30 Y/− mice were given vitamin C-supplemented water in this study. Vitamin C is known to play an important role in the structure and function of mitochondria and endoplasmic reticulum [33]. Harrison et al reported that vitamin E and vitamin C treatment improves fibrosis but not necroinflammation in NASH patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Myofilaments are fragmented and mitochondria swollen (Kim, 1977). Epiphyseal growth centers of long bones are deranged with greatly reduced osteoid formation, degenerating and deranged chondrocytes, decreased bony trabeculae in the marrow cavity, reduced osteoclastic and increased osteoblastic activity, and multiple microfractures.…”
Section: Hypovitaminosis Cmentioning
confidence: 99%
“…A history of inappropriate feed, decreased prothrombin time, and a serum vitamin C level below 0.55 mg/dl (normal around 2.01 mg/dl) indicate hypovitaminosis C (Kim, 1977). A history of inappropriate feed, decreased prothrombin time, and a serum vitamin C level below 0.55 mg/dl (normal around 2.01 mg/dl) indicate hypovitaminosis C (Kim, 1977).…”
Section: Hypovitaminosis Cmentioning
confidence: 99%
“…That is the main reason why guinea pig is widely used laboratory model for examining of the oxidative stress (9)(10)(11). The inability to produce endogenous ascorbic acid makes results from guinea pigs extrapolatable to humans (12)(13)(14). Except the inability to synthesize vitamin C there are other similarities like a similar response of lipid metabolism to dietary intervention (15).…”
Section: Introductionmentioning
confidence: 99%